Cleaning the Oceans: A Pedagogical Practice of Environmental Awareness with Robotics in Early Childhood Education - Silva, Vitor Carvalho; Santana, Lucas Emanoel Ribeiro; Tavares, Raul Silva; Maia, Claudia Juliette do N. Araujo; Teixeira, Waleska R. de L.; Ferreira, Cristiane de Melo; Teixeira, Leonardo R. de L.; Garcia, Luciane Terra dos Santos; Gonçalves, Luiz Marcos Garcia (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
This article analyzes a pedagogical experience carried out with 3- and 4-year-old children from Early Childhood Education, through a pedagogical practice that addresses ocean cleanup, within the scope of the MandacaruBot extension project (EAJ/UFRN). The proposal integrates scientific, environmental, and technological knowledge with the use of sustainable Educational Robotics and unplugged robotics, seeking to promote scientific literacy and computational thinking in a playful and accessible way. The activities involved the construction of artifacts, interactive game, and group discussions, according to the guidelines of the Common National Curriculum Base (BNCC) and the Computing BNCC. In practice, hydraulic arms developed with syringes, gamification, computational thinking, and unplugged robotics were used. The results demonstrated the development of motor, cognitive, and socioemotional skills in children, in addition to engagement with issues of sustainability and citizenship.